Leaf morphospace in Euphorbia tithymaloides (Euphorbiaceae) was likely shaped by evolutionary contingencies rather than climate - Luis Emiliano Jacobo-Arteaga; Max Demián Medina-Rodríguez; Brenda Hernández-Hernádez; Itzel Aurora Piña de la Rosa; N. Ivalú Cacho (Plant Ecology and Evolution, 2022)
Background and aims – Understanding whether variation in plant attributes is primarily driven by selection or historical contingencies is a main goal in evolutionary biology. We characterize leaf diversity in Euphorbia tithymaloides and identify patterns related to taxonomy, geography, biogeography, and climate that provide insights on the role of ecological and evolutionary forces in shaping its leaf diversity. Material and methods – We constructed a leaf morphospace using linear morphometric measurements derived from images (leaf maximum length and width, area, and perimeter), and calculated indexes that reflect aspects of leaf shape (leaf aspect ratio, area-perimeter ratio, obovate index, and circularity). Climatic data were extracted from WorldClim layers based on occurrence data. We visualized leaf and climate spaces with principal components analyses and used Kruskal-Wallis tests, linear models, and Mantel tests to test predictors of leaf variation (taxonomy, geography, climate). Key results – We document differences in the foliar morphospace occupied by subspecies of Euphorbia tithymaloides, and a substantial overlap in the climatic space they occupy, suggesting that foliar differences among subspecies are not likely driven by climate. Foliar morphology can be used as a proxy for subspecies in E. tithymaloides, as taxonomy explains a large proportion of variation in leaf morphology (10–60%). Geography and climate explain a small proportion of foliar variation not explained by subspecies (~3% and 5%, respectively). Temperature, precipitation, and seasonality are the climate variables with most explicative power. Conclusion – Leaf diversity in E. tithymaloides is not driven by climate, instead, it is likely the result of evolutionary contingencies faced by this species throughout its historical range expansion across the Caribbean Basin. This study shows that historical contingencies in addition to selection acting on ecological processes can shape foliar diversity and expand a lineage’s potential to explore morphological and climatic spaces.